Annual trends of human brucellosis in pastoralist communities of south-western Uganda: a retrospective ten-year study - Kansiime, Catherine; Rutebemberwa, Elizeus; Asiimwe, Benon B.; Makumbi, Fredrick; Bazira, Joel; Mugisha, Anthony (Infectious Diseases of Poverty, 2015)
Background: Human brucellosis is prevalent in both rural and urban Uganda, yet most cases of the disease in humans go unnoticed and untreated because of inaccurate diagnosis, which is often due to the disease not manifesting in any symptoms. This study was undertaken to describe trends in laboratory-confirmed human brucellosis cases at three health facilities in pastoralist communities in South-western, Uganda. Methods: Data were collected retrospectively to describe trends of brucellosis over a 10-year period (2003–2012), and supplemented with a prospective study, which was conducted from January to December 2013. Two public health facilities and a private clinic that have diagnostic laboratories were selected for these studies. Annual prevalence was calculated and linearly plotted to observe trends of the disease at the health facilities. A modified Poisson regression model was used to estimate the risk ratio (RR) and 95 % confidence intervals (CIs) to determine the association between brucellosis and independent variables using the robust error variance. Results: A total of 9,177 persons with suspected brucellosis were identified in the retrospective study, of which 1,318 (14.4 %) were confirmed cases. Brucellosis cases peaked during the months of April and June, as observed in nearly all of the years of the study, while the most noticeable annual increase (11–23 %) was observed from 2010 to 2012. In the prospective study, there were 610 suspected patients at two public health facilities. Of these, 194 (31.8 %) were positive for brucellosis. Respondents aged 45–60 years (RR = 0.50; CI: 0.29–0.84) and those that tested positive for typhoid (RR = 0.68; CI: 0.52–0.89) were less likely to have brucellosis. Conclusions: With the noticeable increase in prevalence from 2010 to 2012, diagnosis of both brucellosis and typhoid is important for early detection, and for raising public awareness on methods for preventing brucellosis in this setting.
Keywords: Trends; Brucellosis; Pastoralist communities